(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Bearingless synchronous machine (BSM) is an electrical machine which rotor is suspended by electromagnetic forces (not ball bearings). It allows achieving ultra-high rotation speed and significantly extending area of electric drive application. Nowadays there are different variants of the machines with the structural design and the searching of optimal solution is going on. The basic calculation parameters of bearingless machines are radial forces that can withstand the rotor from external load and torque produced on the shaft. This article describes the theoretical results based on a computer model that produces the finite element method and experimental study of the BSM prototype.